Relationship Between Motivation and Performance in K.C.S.E Biology In Selected Secondary Schools In Nyakach District, Kisumu County, Kenya - Albert, Mr. Owino Ogutu; Osman, Prof. Ahmed; Alice M., Dr. Yungungu; O, Ogolla Bernard (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
This paper identifies and discusses motivation related factors and how they influence performance in K.C.S.E Biology in selected secondary schools in Nyakach Sub – county, Kisumu County. The study was significant as performance in K.C.S.E Biology has been poor over the years; hence need to find out causes. The study was guided by the systems theory advocated by Gagne and Briggs (1979). The research was conducted through descriptive survey design by quantitative and qualitative approach. The target population was seven hundred and thirty Form four students, eighteen Biology teachers, and fourteen Principals. Stratified random sampling was used to select schools, purposive sampling for selecting teachers and Principals, form four students were first stratified then selected through simple random sampling. Data was collected using questionnaires for students, teachers and interview schedule for principals. Descriptive Statistics such as frequencies, percentages, correlation analysis, regression coefficient and coefficient of determination were used to analyze data using Statistical Package for the Social Sciences Programme (SPSS). The finding was that there was positive relationship between motivation and performance in K.C.S.E Biology. The study recommended that, teachers should always introduce motivational variables in their teachings.